Analisis Persepsi Nasabah Terhadap Produk Gadai Emas Pada Pegadaian Syariah di Kota Langsa - Yoesa, Asriandi; Dayyan, Muhammad (Program Pascasarjana IAIN Langsa, 2023)
Financing services with gold pawn contracts provided by the Sharia Pawnshop Unit continue to increase from year to year. People who take advantage of loan funds by pawning gold at Sharia Pegadaian are interesting to analyze. This study aims to analyze two things. First, what is the gold pawn product service process at Pegadaian Syariah West Langsa Unit? Second, what is the customer's perception of gold pawn financing services with the Rahn agreement at the West Langsa Sharia Pawnshop Unit (UPS)? The method used to collect data is through two techniques. Through interviews with three West Langsa UPS managers. Then data was obtained through a questionnaire with a purposive sampling technique from 50 UPS West Langsa customers. Next, the data was analyzed using a qualitative approach. The results of the research found two things: First, the service process and gold pawning practices at UPS Langsa Barat are in accordance with sharia principles and in line with maqashid sharia in the principles of ta'awun and safeguarding assets. Second, the public's perception of gold pawning products at UPS Langsa Barat states that gold pawning services and practices are stated to be based on sharia concepts. All customers who filled out the questionnaire 100% stated that UPS West Langsa's service was friendly with a location that was easy to reach, and 82% stated that the gold pawn product had implemented the ta'awun (please help) principle.